Changes of Physico–Chemical Properties of Pig Slurry During Storage - . Mansyur; Hong L Choi (Media Peternakan, 2011)
This study was aimed to determine changes of the characteristics of raw pig slurry as liquid organic fertilizer at various storage times. A completely randomized design was used in this research. The treatments were storage times, i.e.: 0, 15, 30, 45, and 60 days. Variables observed were loss of the slurry, degree of acidity (pH), electrical conductivity (EC), total solid (TS), volatile solid (VS), total chemical oxygen demand (tCOD), soluble chemical oxygen demand (sCOD), total nitrogen (TN), ammonia-nitrogen (NH3-N), nitrate-nitrogen (NO3-N), total phosphate (TP), and dissolve reactive phosphate (DRP). The results showed that storage time significantly affected all the observed variables, except the concentration of NO3-N and total phosphate content. The pH, TS, VS, DRP, and losses of slurry lost during storage times increased, while EC, TN, NH3-N, tCOD, and sCOD decreased. Physico-chemical properties of slurry during storage times changed, as a result of organic matter breakdown.